Contested body Metaphors of dominion in Romans 5-8 - Potgieter, Annette (HTS Religion & Society Series, 2020)
Within the plenitude of Pauline studies, Contested body: Metaphors of dominion in Romans 5-8 provides a cohesive scholarly investigation into metaphors of dominion employed by Paul. This book advances the understanding that the body is the specific space where forces vie in Romans 5-8.